George Walker papers - Walker, George, approximately 1752-approximately 1817.
Chiefly letters written by Walker to the mercantile firm of Huie, Reid & Company, Dumfries, Va.
Merchant and land speculator of Washington, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Huie, Reid & Company (Dumfries, Va.); Merchants -- Virginia -- Dumfries; Merchants -- Washington (D.C.); Dumfries (Va.) -- Commerce; Virginia -- Commerce; Washington (D.C.) -- Commerce; Merchants; Land speculators